SISTEM INFORMASI PERSEDIAAN DAN PENJUALAN PADA TOKO KRIPIK RUMAH MINANG BERBASIS WEB - Angely Sinaga; Jamaluddin Jamaluddin; Rimbun Siringoringo (Universitas Methodist Indonesia, 2022)
Running a business requires an information technology that encourages people to create new innovations to get information quickly and easily. Advances in information technology are seen increasingly rapidly in the development of the internet in particular. Regarding the internet, it certainly cannot be separated from the name of a website. The website is used to introduce a product or service which is called the promotion of internet users. In the inventory and sales process, the seller markets the product still using a simple and manual method, so that the marketing of products and services is still not optimal. The author in this case the opportunity to make an inventory and sales information system planning based on the specified research results. Planning this system is called a web-based information system, with the aim that customers will be able to access information and buy easily, quickly and precisely and sellers market products easily, It is hoped that this information planning system can be useful for the seller in their business activities. Especially in the inventory and sales department so that the data and information provided are more structured and accurate.